Institutional Change, Policy Challenges, and Macroeconomic Performance : Case Study of the Islamic Republic of Iran (1979-2004) - Hakimian, Hassan (World Bank, Washington, DC, 2017)
Debates over the nature and direction of economic policy in Iran have intensified rather than abated after the tumultuous changes brought about by the revolution in 1979. In the span of these three decades, Iran has witnessed sweeping institutional changes and has been affected by significant economic and political upheavals. At the macroeconomic level, too, there have been a number of shocks ranging from oil booms and busts, to war (with Iraq), trade sanctions, and internal political strife. This paper uses Iran's experience to reflect on growth and development in the context of political upheaval and an uncertain institutional environment. It is a premise of the paper that Iran's recent past presents a rare, 'laboratory' like, case for the study of growth and development in a broad context. This paper examines post-revolutionary Iran's macroeconomic policies and performance in a comparative context, appraising it against Iran's past trends and real potential. It shows how recurrent cycles of populism and pragmatism have characterized this period. The paper argues that two sets of factors have conditioned Iran's performance and will continue to taint her prospects for sustainable growth into the future. These are: (i) Iran's limited economic diversification and continued dependence on the oil sector, and (ii) the institutional setting in which post-revolutionary economic policies have been formulated and implemented for much of the last three decades.